Activity and stability of lipase preparations from Penicillium corylophilum: Potential use in biocatalysis - Romero, Cintia Mariana (2014)
Biocatalysts with lipase activity were produced by Penicillium corylophilum under basal and olive oil-induced conditions. In the presence of olive oil, both the extracellular and the mycelium-bound lipase activities were increased significantly. The four biocatalysts maintained a residual lipase activity after incubation in a wide pH range showing high stability in a defined acidic to neutral pH range. Some differences between biocatalyst residual activities were also observed after incubation at various temperatures or in the presence of organic solvents such as methanol, ethanol, acetone, butanol, hexanol, n-hexane, and heptane. Enzymes which are stable in the presence of ethanol or butanol could be useful in ecofriendly processes for biodiesel production.